Case report: Camrelizumab associated with central retinal vein occlusion - Zhan, Yixiang; Zhao, Weipeng; Ni, Kemin; Liu, Zhaoce; Su, Yanjun; Li, Xichuan; Zhang, Heng; Zhang, Chunze (Frontiers in Immunology, 2022)
Immunotherapy has revolutionized cancer treatment and become one of the five pillars of cancer therapy. The clinical applications of immunotherapy have been adapted to range from the management of melanoma to most tumor types. As the clinical applications of cancer immunotherapies expand, understanding the treatment-related adverse events of these drugs becomes critical in clinical practice. We report a rare case of ocular immune-related side effects associated with camrelizumab that resulted in vision loss. A 56-year-old male patient was diagnosed with small cell lung cancer. The tumor involved the porta pulmonis and mediastinum upon initial diagnosis; therefore, surgery was not possible. Upon receiving the 10th immunotherapy session with camrelizumab 200 mg the patient’s visual acuity decreased in his right eye and a central retinal vein occlusion. Optical coherence tomography revealed significant cystoid exudation in the macular area and vitreous hemorrhage. The patient underwent phacoerysis and intraocular lens implantation after symptom onset. Following surgery, the patient's vision was limited restored. This is the first clinical report in China of central retinal vein occlusion and vitreous hemorrhage associated with anti-PD-1 therapy, ultimately leading to blindness. Although rare, clinical practitioners should be concerned about ocular adverse events associated with anti-PD-1 immunotherapy and develop a high index of suspicion for this possibility, since ophthalmic manifestations that are rapidly detected, closely monitored, and appropriately managed are treatable.